PENGARUH DUKUNGAN SOSIAL TERHADAP KEMAMPUAN SOSIALISASI ANAK BERKEBUTUHAN KHUSUS - Nani, Desiyani; Ekowati, Wahyu; Hara Permana, Ryan (Jurnal Ilmiah Kesehatan Keperawatan, 2013)
Children with special needs usually take many pshycological problems caused by social respons on their dissability. Support from society on them will be useful for their skills development (Efendi, 2008).This research was aimed to identify socialization skills between special needs children and also normal children and how them receive social support especially from their parents. This is descriptive analitical research withcross sectional approach. Undertake in school of special needs children ini SLB Yakut, Purwokerto dan SDN 04 GrendengPurwokertoheld in July-Agustus 2010, take 16children with special needs and 11normal children fromi SD Grendeng. There were two variable measured : social support and social skills. The result were social skills on the children with special needs were 14 children in good category, and 2 children was not. All of normal children have good category of socialization skills (100%). Keyword: children with special needs, social support, socialization skills